Conceptual Analysis of Emotional Control in the Al-Quran (Thematic Study of Verses on Anger with Patience in Tafsir Al-Azhar) - Muhammad Renaldi; Budimansyah; Masruchin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research discusses the concept of anger emotional control, a phenomenon that often occurs in the scope of society related to fellow humans, as a person easily vents his anger against anyone without accurate prevention and handling both verbally and nonverbally and how these topics will be discussed. Regarding the emotion of anger, it can usually be understood as bad behavior such as saying rudely, hitting, and showing scary expressions, with the guidance of lust al-anger can result in evil, for someone who cannot control his anger will fall into a loss. The definition of this assumption has been developed and found in dictionaries as well as current indexes. As a source of guidance for Muslims, the Qur'an provides many explanations about the emotion of anger in the focus of the term Ghadab and Ghilzah, so that this verse is easy for everyone to understand, of course it needs to be interpreted clearly and concisely. Therefore, the author here would like to try to offer a clear and concise explanation of the problem of conceptual control of anger emotions from the perspective of Prof. Dr. H. Abdul Malik Karim Amrullah in the tafsir of Al-Azhar, regarding the analysis of anger emotions in the Tafsir Al-Azhar and the stages of controlling the emotions of anger in the Quran according to the Tafsir Al-Azhar. This research is library research, for which the author takes steps to identify, collect, process and study existing data related to anger emotions, both in the form of primary and secondary data accurately and factually. Meanwhile, the secondary data in question are other literature in the form of research books and other articles which of course are related to the problem of controlling anger emotions in the Qur'an and Tafsir Al-Azhar. This study found several conclusions that the Qur'an describes anger in various terms, but the researcher's focus is on the terms ghadab and ghilzah. A more actual understanding of anger recognizes that this trait does have a place in certain situations, but it doesn't always have to be expressed physically. Often, it takes an internal effort to overcome it. The concept of anger is not only limited to its literal meaning, but it is also understood as a condition that has the potential to bring harm, which can cause a person to deviate from the truth. And according to the tafsir of Al-Azhar by Buya Hamka, the stages of controlling the emotion of anger are by dhikr to Allah, being patient, forgiving others, and doing ihsan, that is, always doing good to others.